(untitled) (Research, Society and Development, 2022)
Blood transfusion is an effective therapeutic method used in cases of large-volume hemorrhages, cancer treatments, coagulopathies, among other causes. However, it can cause risks such as allergic reactions, febrile and circulatory volume overloads. The aim of this research is to analyze the occurrences of transfusion reactions in patients receiving blood components, identifying the frequency of the main immediate reactions, as well as severity and associated factors. This is a retrospective and descriptive study about blood transfusions and transfusion reactions that occurred in patients admitted to the Southwestern Regional Hospital Dr Walter Alberto Pecóits (HRSWAP) from 2018 to 2020. The variables collected included age, gender, unit of occurrence, diagnostic hypothesis at admission, signs and symptoms observed, time of onset of manifestations, severity and type of hemocomponent. In total, 1,837 patients were blood transfusion recipients from 2018 to 2020. A total of 16 immediate transfusion reaction forms were identified, in which the most frequent clinical manifestations were: body temperature elevation in at least 1ºC (75%), shorthand (25%), hypertension (18.75%) and hives (18.75%); 93.75% of the reactions classified as mild. Moreover, most of the reactions occurred in transfusions to patients who were in the Surgical Clinic and Urgency and Emergency sectors, reference areas for the service studied. In addition to verifying the indications and transfusion reactions, the study presented limitations related to the inadequate filling out of the notification forms. Thus, the work becomes relevant by attracting visibility to good hemotherapeutic conducts, considering the specificities of the hospital addressed.